A complexity approach to explaining the origins of life - Carlos Eduardo Maldonado (Cogent Arts & Humanities)
This article proposes an explanation of the origin of life in terms of complexity science. It argues that the origin of life on Earth is one and the same process with the origin of the biosphere—as a living organism. Therefore, the argument consists in bringing together geology and microbiology. Thus, any reductionist approach, say physicochemical, biophysical or biochemical—which are the standard explanations about the origins of life, become untenable. Understanding the origins of life and what living beings do to live is thus one and the same question. Nonetheless, three serious obstacles are to be overcome, namely Plato’s philosophy, Aristotle’s logic and Descartes’ science. Life is a self-organizing system or also autopoietic, a twofold approach that helps explain why and how living beings arose. We need redefine the interactions between geology and microbiology while keeping in mind that the evolution of life is a historical process. There exist currently more than one hundred definitions of life and yet, none is correct.